Aristotle's Inner Logic of Justice: Based on the Nicomachus Ethics - Shu, Wang (Transactions on Social Science, Education and Humanities Research, 2024)
Aristotle discusses the issue of justice in Volume V of the Nicomachan Ethics, including the connotation of justice, several types of justice, and the relationship between justice and willing behavior. Aristotle seems to have no rules and regulations in his discourse, but in fact, he has his inherent logic. Aristotle first provides a specific explanation of justice and divides it into overall justice and specific justice. Overall justice is related to virtue, reflecting more of an individual's quality and possessing individuality; The specific justice is closely related to the life of the city-state, and is also the main object of discussion by the Aristocrats. The purpose of discussing justice is also for the overall happiness of the city-state. It is not difficult to see the city-state nature of the justice it discusses, and natural justice and agreed justice are closely related to the evolution of the city-state. Finally, Aristotle brought justice back to the individual, exploring the relationship between justice, injustice, and willful behavior, returning to individuality, which is also the individuality in the city-state. It can be said that Aristotle's theory of justice is interpreted along the internal logic of individuality, city-state, and individuality. However, at the same time, city-state cannot represent complete justice and happiness, so justice ultimately returns to the soul quality of the individual. Justice is the manifestation of individual virtue in the city-state, and city-state and individuality complement each other to achieve the goal of justice - the happiness of the political community.